Effects of bilingual language exposure on toddlers with autism spectrum disorder - Phillips, Sarah; Yanchik, Amelia; Jung, Heather; Vietze, Peter; Lax, Leah Esther (Frontiers in Psychology, 2024)
Research analyzing the effects of bilingual language exposure on children with autism spectrum disorder (ASD) has increased in frequency. Utilizing the Bayley Scales of Infant and Toddler Development—Third Edition, the current study analyzed the effects of bilingual language exposure and age on language development, cognitive development, and social emotional development in toddlers with ASD. Older children demonstrated higher language scores than younger children. The interaction between ASD and bilingualism did not yield statistical significance for language, cognitive, or social emotional scores; however, the interaction between age and bilingualism was found to be significant. Age may have more of an influence on language development than ASD. Children with ASD can be raised in bilingual homes without affecting long-term development.